MiR-200c-3p Regulates DUSP1/MAPK Pathway in the Nonalcoholic Fatty Liver After Laparoscopic Sleeve Gastrectomy - Zhang, Tao-tao; Wang, Yong; Zhang, Xiang-wen; Yang, Ke-yu; Miao, Xiu-qin; Zhao, Guo-hua (Frontiers in Endocrinology, 2022)
Aim: Non-alcoholic fatty liver disease (NAFLD) is a health burden worldwide, which is closely related to obesity. The effect of sleeve gastrectomy (SG) on NAFLD is efficient, and the underlying mechanism remains unknown. Our study sought to investigate the mechanism of dual-specificity protein phosphatase 1 (DUSP1) expression regulation following the SG procedure in NAFLD patients and C57BL/6J mice via miR-200c-3p. Methods: The serum was extracted from NAFLD patients who underwent laparoscopic sleeve gastrectomy (LSG) and volunteers. Next, the correlation between miR-200c-3p and DUSP1 was identified in vitro. NAFLD mice were modelled by high-fat diets (HFD). The hepatic tissue expression levels of miR-200c-3p, DUSP1, phospho-extracellular regulated protein kinases1/2（p-ERK1/2）, phospho -p38 mitogen-activated protein kinases (p-p38), and phospho-c-Jun N-terminal kinases (p-JNK) induced by SG procedure were evaluated. Results: The SG procedure contributed to significant weight loss, reduced lipids in NAFLD patients and mice. The increased expression level of miR-200c-3p and reduced expression of DUSP1 were observed in NAFLD patients and mice (p<0.05). The reduced expression levels of miR-200c-3p and increased expression of DUSP1 were observed in patients and mice with NAFLD who underwent SG procedure. DUSP1 is a potential target of miR-200c-3p. Conclusions: A novel mechanism was identified in which miR-200c-3p regulates the MAPK-dependent signals that are linked to the promotion of hepatosteatosis via DUSP1 after sleeve gastrectomy. The findings suggested that miR-200c-3p should be further explored as a potential target for the treatments of NAFLD.